Tughril Beg: Architect of Seljuk Power in the Middle East - Sahal, Moch. Fahmi; Ubaidillah, M. Khafidz; Kriswanda, Rafi Bayu (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Tughril Beg, the founder of the Seljuk Dynasty, was an influential figure in the development of Islamic civilization in the Middle East during the 11th century, amid the declining authority of the Abbasid Caliphate and the increasing fragmentation of regional power. This study aims to examine the origins of Tughril Beg’s rise and his contributions in the political, military, and religious spheres within the Seljuk Dynasty. The method used is historical-qualitative with a descriptive-analytical approach, based on literature review of primary and secondary sources. The findings show that Tughril Beg succeeded in consolidating fragmented territories, gaining legitimacy from the Abbasid Caliph, and protecting and strengthening Sunni institutions. His role in establishing a stable system of governance and regional stability paved the way for sustained scientific and cultural revival.